Experiences of frontline healthcare workers and their views about support during COVID-19 and previous pandemics: a systematic review and qualitative meta-synthesis - Billings, Jo; Ching, Brian Chi Fung; Gkofa, Vasiliki; Greene, Talya; Bloomfield, Michael (BMC health services research, 2021)
Background Healthcare workers across the world have risen to the demands of treating COVID-19 patients, potentially at significant cost to their own health and wellbeing. There has been increasing recognition of the potential mental health impact of COVID-19 on frontline workers and calls to provide psychosocial support for them. However, little attention has so far been paid to understanding the impact of working on a pandemic from healthcare workers’ own perspectives or what their views are about support. Methods We searched key healthcare databases (Medline, PsychINFO and PubMed) from inception to September 28, 2020. We also reviewed relevant grey literature, screened pre-print servers and hand searched reference lists of key texts for all published accounts of healthcare workers’ experiences of working on the frontline and views about support during COVID-19 and previous pandemics/epidemics. We conducted a meta-synthesis of all qualitative results to synthesise findings and develop an overarching set of themes and sub-themes which captured the experiences and views of frontline healthcare workers across the studies. Results This review identified 46 qualitative studies which explored healthcare workers’ experiences and views from pandemics or epidemics including and prior to COVID-19. Meta-synthesis derived eight key themes which largely transcended temporal and geographical boundaries. Participants across all the studies were deeply concerned about their own and/or others’ physical safety. This was greatest in the early phases of pandemics and exacerbated by inadequate Personal Protective Equipment (PPE), insufficient resources, and inconsistent information. Workers struggled with high workloads and long shifts and desired adequate rest and recovery. Many experienced stigma. Healthcare workers’ relationships with families, colleagues, organisations, media and the wider public were complicated and could be experienced concomitantly as sources of support but also sources of stress. Conclusions The experiences of healthcare workers during the COVID-19 pandemic are not unprecedented; the themes that arose from previous pandemics and epidemics were remarkably resonant with what we are hearing about the impact of COVID-19 globally today. We have an opportunity to learn from the lessons of previous crises, mitigate the negative mental health impact of COVID-19 and support the longer-term wellbeing of the healthcare workforce worldwide.